Piecewise Parabolic Approximation of Plane Curves with Restrictions in Computer-Aided Design of Road Routes - Struchenkov, Valery I (Transactions on Engineering and Computing Sciences, 2013)
Approximation problems of plane curves, which are set as a sequence of points arise in computer-aided design of roads. Approximating curve consists of the elements: straight-line and parabolas segments. The parameters of these elements are constrained. Moreover, the number of elements is unknown. This article deals with the problem of per-element approximation, in which the elements must meet to the restrictions of special kind. This problem arises in computer-aided design of the longitudinal profile of road. The problem is solved by dynamic programming.